Analisis Efektivitas Instagram Sebagai Media Promosi pada Café Omah Bingen di Kecamatan Indralaya Utara - Lestari, Ester; Ginting, Gina Perwiinta Br Ginting; Mutiara Hati; Harish Jourdan Syahfikri (Program Studi Agribisnis, Universitas Muhammadiyah Sukabumi, 2026)
This study aimed to analyze the effectiveness of Instagram as a promotional medium for Café Omah Bingen in Indralaya Utara. The research employed a quantitative approach using a structured questionnaire distributed to 36 respondentslwho had interacted with the café’s Instagram account. The results of multiple linear regression showed that the quality of content andlcustomer engagement had a positive and significant influence on consumers’ purchase decisions. Both variables were found to contribute to increased interest and intention to visit the café. The analysis also indicated that Instagram promotion accounted for 45.1% of the variation in consumer purchase decisions, while thelremaining 54.9% was influenced by external factors beyond the model. Overall, the findings suggest that Instagram serves as a relevant and supportive promotional tool for enhancing consumer attraction, although it is not the sole determinant of purchase decisions.